Knowledge Diversity at Universities? A critical analysis of changing post-digital knowledge ecologies using examples from Austria, Germany, and Italy - Gross, Barbara; Hug, Theo; Stadler-Altmann, Ulrike (Seminar.net, 2025)
In the last decade, debates on digitalization programs and on dynamics of datafication have become increasingly influential at universities. More recently, debates on the importance of artificial intelligence (AI) have begun, although corresponding questions about changing knowledge ecologies are currently underexplored in educational research. The processes of changing knowledge production are encountering relatively entrenched structures of knowledge organization and communication at universities, which are struggling to handle these new challenges. In this paper we use the historically-shaped university organization structures in three European countries as cases of analysis. Thus, first we give an overview of the concepts of knowledge ecology and knowledge diversity, followed by, second, a critical discussion of current trends in the digitalization and datafication of scientific knowledge production in education with examples from Italy, Austria and Germany, The choice of these different and highly complex scientific systems is justified by our experiences in these diverse contexts and corresponding academic affiliations. Third, we reflect on the implications of changing knowledge ecologies and knowledge diversity for the future of higher education.